(3GdGNJHGQGJ GdYdejIs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3eMeO Hf eMehO Hf GdJdGejP GdJQcRi GdTfbjWi s)
(3ChdgG (B:s
(3HOC HcJGH GdWgGQI , HGH GdejGg GdWgGQI JGQI Jchf ef GdCYjGf GdfLSI hJGQI ef GdYeGd GdNHjKI s
(3BNQgG (B:s
(3aEPG bGd ef hGMO Edi YTQI dReg NeSI hNeShf Gf GONdfG GdWQajf s
(3HgG fXGe GdJYbjHIs
(3ai fgGjJg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
Keywords: (3Gdabg GdMfHdjs